Contemporary environment and historical legacy explain functional diversity of freshwater fishes in the world rivers. Issue 4 (16th February 2022) - Su, Guohuan; Tedesco, Pablo A.; Toussaint, Aurèle; Villéger, Sébastien; Brosse, Sébastien
Abstract: Aim: Regional taxonomic diversity (species richness) is strongly influenced by a joint effect of the current processes (habitat and energy availability) and historical legacies (past climate and geography), but it is still unclear how those historical and current environmental drivers have shaped the functional diversity of species assemblages. Major taxa studied: Freshwater fish. Location: Global. Time period: 1960s–2000s. Methods: We combined the spatial occurrences over 2, 400 river basins world‐wide and the functional traits measured on 10, 682 freshwater fish species to quantify the relative role of the habitat, climate and historical processes on the current global fish functional diversity. To avoid any correlation between taxonomic diversity and functional diversity, we controlled for differences in the number of species (species richness) between rivers. Functional diversity was considered through three complementary facets: functional richness, functional dispersion and functional identity. Results: The habitat‐related variables explained most of the gradient in functional richness, verifying the habitat size–diversity hypothesis. In contrast, the historical climate–geography legacies markedly imprinted the functional dispersion and functional identity patterns, leading to a balanced influence of the current and historical processes. Indeed, the distribution of morphological traits related to fish dispersal was explained largely by the glaciation events during the Quaternary, leading to strong latitudinal gradients. Main conclusions: This study provides new insights into the role of historical and current environmental determinants on the functional structure of fish assemblages and strengthens the proposal that the independence of facets of functional diversity from the species richness makes them essential biodiversity variables to understand the structure of communities and their responses to global changes.